2006
DOI: 10.1136/jcp.2006.039917
|View full text |Cite
|
Sign up to set email alerts
|

Pax-5 immunoexpression in various types of benign and malignant tumours: a high-throughput tissue microarray analysis

Abstract: Despite its expression in a small subset of malignancies of epithelial origin, Pax-5 is still a good and reliable immunomarker in diagnosing B-NHL, HL and neuroendocrine carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 21 publications
7
63
0
3
Order By: Relevance
“…This is supported by expression data from the gene expression database Oncomine, which indicated that PAX5 expression is positively correlated with breast cancer metastasis in three studies (28,30,31). In contrast, an immunohistochemical study conducted by MhawechFauceglia et al (52) detected PAX5 in only one case out of 164 benign and malignant tumor samples. However, Mhawech-Fauceglia et al also failed to observe expression of PAX5 in cases of astrocytomas, medulloblastomas, and neuroblastomas, whereas several other studies have shown expression of PAX5 mRNA in these three pathologies (14)(15)(16).…”
Section: Discussionmentioning
confidence: 61%
“…This is supported by expression data from the gene expression database Oncomine, which indicated that PAX5 expression is positively correlated with breast cancer metastasis in three studies (28,30,31). In contrast, an immunohistochemical study conducted by MhawechFauceglia et al (52) detected PAX5 in only one case out of 164 benign and malignant tumor samples. However, Mhawech-Fauceglia et al also failed to observe expression of PAX5 in cases of astrocytomas, medulloblastomas, and neuroblastomas, whereas several other studies have shown expression of PAX5 mRNA in these three pathologies (14)(15)(16).…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have identified that the PAX5 gene, which is located on chromosome 19p13 (Stapleton et al, 1993;Kovac et al, 2000), is associated frequently with chromosomal translocations (Busslinger et al, 1996). Aberrant PAX5 expression has been reported in several tumors (Baumann Kubetzko et al, 2004;Meza et al, 2006;Mhawech-Fauceglia et al, 2007;Lazzi et al, 2009), thus dysregulated expression of PAX5 is likely to be involved in carcinogenesis and the malignant progression of human cancers. A recent study demonstrated that the lack of expression of PAX5 in lymphoid neoplasms is associated with promoter hypermethylation, and cases with PAX5 silence were characterized by poor clinical outcome (Lazzi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Eventually 763 cases of cutaneous Merkel cell carcinoma were retrieved from the English literature and included in our review. 15,[18][19][20][21][22][23][24][25][26][27][28][29] …”
Section: Case Selectionmentioning
confidence: 99%
“…We also studied expression of PAX5 and TdT in our cases; both markers have been detected in the majority of cutaneous Merkel cell carcinomas. [18][19][20][21][22] …”
mentioning
confidence: 99%